Plan de manejo de residuos sólidos para la mejora de la gestión ambiental en un establecimiento industrial pesquero, Chicama, 2019 - Alcalde Silva, Wendy Estefany (2020)
In the present research work, a solid waste management plan was carried out to improve environmental management in a fishing industrial establishment. The methodology applied consists of different stages: The first, make a diagnosis of the current situation of solid waste, its characterization and identification of environmental impacts through a matrix system. Subsequently, the design and implementation of the solid waste management plan were carried out. Workers were trained on the following topics: Integral management of solid waste, legislation applicable to solid waste management, as well as, minimization and segregation of solid waste, obtaining an improvement in knowledge of 79.55%, 100% and 93.77%, respectively. Likewise, with respect to the correct segregation of solid waste, an average improvement of 22.66% was achieved. In addition to this, paper consumption was reduced during the first month by 22%, 48% in the second and 51% in the third. Therefore, the improvement of environmental management in the company COPEINCA S.A.C. was achieved